Determinants of banks’ cost efficiency: a case study of selected commercial banks, Ethiopia - Astereye Enyew Ereta; Eshetu Yadecha Bedada; Tesfaye Ginbare Gutu (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
This study examines the determinants of cost efficiency commercial banks’ in Ethiopian using balanced panel data with a sample of 13 commercial banks over the period 2010-2017 by paying a translog stochastic cost frontier approach. The identification and selection of inputs and outputs variables was based on the intermediation approach. Accordingly, three input variables (cost of labor, cost of capital, and cost of fund) and two output variables (total loans and other earning assets) are used in the study. Furthermore, five banks specific and one macroeconomic variable are included to examine their effect on cost efficiency. So as to examine the effect of determinant variables which are associated with banks efficiency, a single stage maximum likelihood estimation method is applied to stochastic frontier cost function. The empirical estimations were accomplished by Appling a single stage maximum likelihood function assimilated into Stata software. The estimation is based on conditional mean model concepts. The finding shows that from bank specific factors, return on assets (ROA), and intermediation ratio have positive and significant for intermediation (IR) and insignificant for ROA with cost inefficiency. On the other hand, Bank size (lnTA), Credit risk (CR) and capital adequacy ratio (CAR) have a significant negative coefficient with cost inefficiency. GDP also has negative but insignificant with inefficiency. Therefore, banks are recommended to improve and sustain their efficiency by maintaining available proportion of capital adequacy ratio and attract high value, low interest-bearing demand deposits.